Effects of reading interventions implemented for upper elementary struggling readers: A look at recent research - Donegan, Rachel E.; Wanzek, Jeanne (Reading & writing, 2021)
In this study, we conducted a review of reading intervention research (1988–2019) for upper elementary struggling readers and examined intervention area (e.g., foundational, comprehension, or multicomponent) and intensity (e.g., hours of intervention, group size, and individualization) as possible moderators of effects. We located 33 studies containing 49 treatment-comparison contrasts, found small effects for foundational reading skills ( g = 0.22) and comprehension ( g = 0.21), and decreased effects when considering standardized measures only. For intervention area, only multicomponent interventions predicted significant effects for both comprehension and foundational outcomes. For intensity, we did not find systematic evidence that longer or individualized interventions were associated with larger effects. However, interventions implemented in very small groups predicted larger comprehension outcomes. Overall, more research examining the quality of school provided reading instruction and how the severity of reading difficulties may impact effects of more intensive interventions is needed.